THE ACTIVITIES WITH GIFTED CHILDREN AT ‘SUMMER PHYSICAL AND MATHEMATICAL SCHOOL’ - Latipov, Zagir Azgarovich (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
The article deals with the theory and the methods for gifted students’ development using the extracurricular activities on their vacation. The Summer physical and mathematical school program, arranged by the Campus of Yelabuga of Kazan (Volga) Federal University is discussed. Purpose. To show the innovative educational project’s experience of The Yelabuga campus Kazan (Volga) Federal University «Summer Physical and Mathematical School». Methodology. The design of the organizational and educational space of students. Results. The study shows The necessity of the special didactic conditions for the gifted child development. It requests the sorting students ( the competitions and contests winners on physics, mathematics and computer science); using the brainstorming method for the theoretical and practical problem solutions during classes; educational activities and games at the subject area; carrying out intermediate and final subject competitions and contests. Staying at summer school, a mutual dialogue, communication with teachers and mentors, the environment must be psychologically comfortable environment for students, taking into account their giftedness, characteristics and tendencies. Practical implications. Developed and successfully tested innovative educational project could be the basis for improving the technical preparation of pre and profile of students.